Full Tensor Gradient of Simulated Gravity Data for Prospect Scale Delineation - Hendra Grandis; Darharta Dahrin (Journal of Mathematical and Fundamental Sciences, 2014)
Gravity gradiometry measurement allows imaging of anomalous sources in more detail than conventional gravity data. The availability of this new technique is limited to airborne gravity surveys using very specific instrumentation. In principle, the gravity gradients can be calculated from the vertical component of the gravity commonly measured in a ground-based gravity survey. We present a calculation of the full tensor gradient (FTG) of the gravity employing the Fourier transformation. The calculation was applied to synthetic data associated with a simple block model and also with a more realistic model. The latter corresponds to a 3D model in which a thin coal layer is embedded in a sedimentary environment. Our results show the utility of the FTG of the gravity for prospect scale delineation.